Investigating the Correlation Between Vocabulary Knowledge and Reading Comprehension in Expository Text of Senior High School Students - Zahra, Aisyah Fairuz; Zuhri, Fauris (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Reading is one of the essential skills to develop their language learning. For senior high students, they need to comprehending the text, particularly expository text. However, many students struggling with reading comprehension due to their limited vocabulary knowledge. Therefore, this research aimed to investigate the senior high school students’ vocabulary knowledge in relation with reading comprehension, specifically in the context of expository text. A quantitative correlational research design was employed in this study, involving 65 students in the tenth grade from a state school in Surabaya, selected through convenience sampling. The researcher administered two tests, such as The Updated Vocabulary Level Test (TUVLT) by Paul Nation and reading comprehension test focusing on expository text to the participants involved in this research. The results revealed that the Pearson Product-Moment correlation value was 0.792 (r value). It showed that students’ vocabulary knowledge and their expository text reading comprehension were positive and strongly correlated. Drawing on these findings, it can be concluded that students with higher vocabulary knowledge are more likely to perform greater in reading comprehension tasks.